The Effect Of The Health Belief Model Approach On The Prevention Of Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome In Pregnant Women - Wida Rahma Arwiyantasari; Budi Laksana (STRADA : Jurnal Ilmiah Kesehatan, 2020)
East Java Province is in the top five in which the population is infected with HIV and it is dominated by men. This will worsen the condition of women if infected with pregnant women, so that the pregnant women are also affected by HIV/AIDS infection. The objective of this study was to analyze the effect of the Health Belief Model approach on the prevention of HIV/AIDS in pregnant women in Madiun City. This type of research was an observational analytic study. The sampling technique used total sampling. The sample size was 80 pregnant women in Madiun City who carried out HIV/AIDS testing. The data collection tool used a questionnaire. The data analysis used Chi-Square and Multiple Logistic Regression analysis. There was a statistically significant effect. Perceived severity, perceived barriers, perceived vulnerability, and perceived benefits affect pregnant women in preventing HIV/AIDS